Daytime transmission of filariasis caused by nonperiodic form of Brugia Malaya among Dayak indigenous inhabitants in East Kalimantan. - FA Sudjadi FA Sudjadi (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 1997)
In addition to the previously known of subperiodic and periodic form, the nonperiodic form of B. malayi Lichtenstein was recently reported from East Kalimantan as a new filarial different subspecies. The morphology or natural habitat of filarial parasite was recently described. This paper reports daytime transmission of the disease found in highly endemic area of Dayak, indigenous inhabitants of Krayan area, Long Ikis district, Pasir regency, East Kalimantan. To show such transmission, the microfilaria carrier was followed by daily activities at daytime. When the carrier was at work in the forest, the wild mosquitoes landing and feeding on him were collected, then reared in a laboratory until 14 days. The remains alive of mosquitoes were then morphologically identified and dissected. Infective larvae were recovered from 2 dissected mosquito species, Mansonia bonnae and Mansonia uniformis. Out of 131 alive mosquitoes dissected, 15 (consisting of 10 Ma.bonneae or 13,0% and 5 Ma. uniformis or 11,6%) were found infectious, from which 23 recovered and 11 filarial larvae respectively. Totally, 34 infective B.malayi larvae recovered: 24 larvae from the head and another 10 from the thorax.Key words: Brugia malayi - nonperiodic form - daytime transmission - Mansonia bonnae - Mansonia uniformis